Contemporary Chaos and Muslim Youth: Getting beyond Defensiveness and Confronting Our Own Demons (American Journal of Islam and Society, 2005)
Why should I, your after-dinner speaker, a time for dessert – for sweetness– be the bearer of exclusively bad news, of chapters from the contemporarychaos that seemingly surrounds us. “The Darkness that Surrounds Us,” tocall upon the words of a great American poet Robert Creeley, who, I imagine,never would have imagined that his own troubling personal visionwould become an easily recognized metaphor to be invoked, as I invoke it,at a gathering of Muslim social scientists. Well, there are some good signs,like a nice after dinner mint that one discovers tucked just under one’s plateat the end of the meal, and I will get to them.My assumption is that I am really not here to tell you of things youknow, living as you do in the United States … things you know far betterthan I, particularly since, as a journalist, I feel on safest ground when I reportto you from personal experience. I cannot and will not even begin to addressthe many moments of humiliation and pain that many American Muslimshave experienced in the backlash to 9/11 and the events that have followed,precisely because I have been personally spared any those experiences. So,I will address experiences from which I have not been spared.I have lived abroad, in what could be called the Arab-Islamic world, forforty years. And for me, the trajectory of contemporary chaos and the crisisconfronting the Muslim youth has been a long one, long before 9/11. Morethan half of those years in the Middle East were spent as a journalist, mainly ...